Keeping one’s seat: the competitiveness of MP renomination in mixed-member electoral systems - Baumann, Markus; Debus, Marc; Klingelhöfer, Tristan (The journal of politics, 2017)
Mixed-member electoral systems are supposed to simultaneously produce coherent parties and ensure the representation of local interests. Whether these goals are achieved depends on the ability of parties and districts to control members of parliament (MPs). We regard the competitiveness of MPs’ bids for renomination as a crucial indicator of the degree to which MPs are punished when deviating from the interests of their principals. The theoretical account we develop makes the competitiveness of MP renomination conditional on the characteristics of the electoral system, the candidate selection regime, an MP’s parliamentary behavior, government status, and district characteristics. Corroborating our expectations, the analysis of the candidate selection processes in the run-up to the 2013 German Bundestag election shows that an increasing degree of ideological deviation from the party line—as expressed in parliamentary speeches—results in a worse position on the party list for opposition MPs but does not affect the renomination of list candidates from the government camp or district candidates.
Gesehen am 22.01.2018